2023
DOI: 10.3390/f14020350
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chrysoporthe deuterocubensis Canker Disease on the Chemical Properties and Durability of Eucalyptus urograndis against Wood Rotting Fungi and Termite Infestation

Abstract: In this study, the effects of stem canker disease caused by Chrysoporthe deuterocubensis on the chemical properties and durability of a Eucalyptus hybrid (E. urophylla x E. grandis) were investigated. Eleven-year-old healthy and infected trees were collected. The samples were grouped into four different classes based on the infection severity: healthy (class 1), moderately infected (class 2), severely infected (class 3), and very severely infected (class 4). The changes in chemical properties were evaluated vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The findings of another study [12] showed that the Eucalyptus hybrid wood infected by the Chrysoporthe deuterocubensis canker disease demonstrates improved biological durability.…”
mentioning
confidence: 99%
“…The findings of another study [12] showed that the Eucalyptus hybrid wood infected by the Chrysoporthe deuterocubensis canker disease demonstrates improved biological durability.…”
mentioning
confidence: 99%